An exploration of the exit plans of the beneficiaries of the foster care grant in Soweto. - Rembuluwani, Rendani (My University, 2014)
Most social assistance programmes have exit strategies in place which require beneficiaries to end their participation in the programme either on an involuntary or voluntary basis. This can occur when the socioeconomic circumstances of the recipients have improved so they accomplish programme objectives and no longer need programme benefits (World Bank, 2000). Despite this ideal of being able to exit the grant system it seems that the withdrawal of the foster care grant can erode quality of life, particularly in circumstances where the foster parents do not have exit plans put in place. The aim of the study was to explore the exit plans of the recipients of the foster care grant in Soweto and the challenges they face in coming up with these plans. The study adopted a qualitative approach and it was exploratory in nature. Ten foster parents and four key informants from the Department of Social Development were selected using purposive sampling. Data were collected using two separate semi-structured interview schedules for participants and key informants. The data gathered was then analysed using thematic content analysis. The results of the study revealed that there was little knowledge and understanding about the foster care grant and what it seeks to do. The study also revealed that there were no exit plans put in place by foster parents. These results of the study found that the participants had very little knowledge of what an exit strategy was and they did not have set exit plans to exit the grant. Other findings indicated that there was no support for participants from their social workers in terms of the sharing of information and the development of exit plans. This study will thus contribute to the discourse on social assistance in general and foster care grants in particular. Furthermore, it will help to sensitise social workers on the need for exit plans for the recipients of foster grants.
Keywords: Foster care; Foster care grant; Recipients; Exit strategies; Poverty